Healthy Eating: No-Cook Breakfast Ideas - Emily Minton (EDIS)
Sometimes we get up and don't feel like cooking breakfast. For those days, here are a few no-cook breakfast ideas. Add a healthy beverage, such as a glass of low-fat milk or 100% fruit or vegetable juice, for a complete meal. This 1-page fact sheet was written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, May 2012.